Between the Danube and the Deep Blue Sea: Zooarchaeological Meta-Analysis Reveals Variability in the Spread and Development of Neolithic Farming across the Western Balkans. (15th September 2016) - Orton, David; Gaastra, Jane; Linden, Marc Vander
The first spread of farming practices into Europe in the Neolithic period involves two distinct 'streams', respectively around the Mediterranean littoral and along the Danube corridor to central Europe. In this paper we explore variation in Neolithic animal use practices within and between these streams, focusing on the first region in which they are clearly distinct (and yet still in close proximity): the western Balkans. We employ rigorous and reproducible meta-analysis of all available zooarchaeological data from the region to test hypotheses (a) that each stream featured a coherent 'package' of herding and hunting practices in the earliest Neolithic, and (b) that these subsequently diverged in response to local conditions and changing cultural preferences. The results partially uphold these hypotheses, while underlining that Neolithisation was a complex and varied process. A coherent, stable, caprine-based 'package' is seen in the coastal stream, albeit with some diversification linked to expansion northwards and inland. Accounting for a severe, systematic bias in bone recovery methodology between streams, we show that sheep and goats also played a major role across the continental stream in the earliest Neolithic (c.6100–5800 BC). This was followed by a geographically staggered transition over c.500 years to an economy focused on cattle, with significant levels of hunting in some areas – a pattern we interpret in terms of gradual adaptation to local conditions, perhaps mediated by varying degrees of cultural conservatism. Subsequent westward expansion carried with it elements of this new pattern, which persisted through the middle and late Neolithic.